2013
DOI: 10.3389/fpsyg.2012.00556
|View full text |Cite
|
Sign up to set email alerts
|

Learner-Controlled Self-Observation is Advantageous for Motor Skill Acquisition

Abstract: There were two main objectives of this research. First, we wanted to examine whether video feedback of the self (self-observation) was more effective for motor skill learning when the choice to view the video was provided to the learner (learner-controlled, LC) as opposed to an experimenter-controlled (EC) delivery. Secondly, we explored whether there were differences in the self-regulatory processes of self-efficacy and intrinsic motivation, as well as perceived choice between the LC and EC conditions. Two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 40 publications
8
67
3
2
Order By: Relevance
“…Interestingly, we found no support that exercising choice, whether relevant or irrelevant to the to-be-learned task, is more autonomy-supportive than not exercising choice. This finding is consistent with Ste-Marie et al (2013), who found no differences in perceived competence between their self-…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we found no support that exercising choice, whether relevant or irrelevant to the to-be-learned task, is more autonomy-supportive than not exercising choice. This finding is consistent with Ste-Marie et al (2013), who found no differences in perceived competence between their self-…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the learner detects errors in their performance by a comparison between motor experience and the objective visual perception of their own performance. In a previous study on the effect of video feedback by self-action observation, Ste-Marie et al (2012) reported an effect on a task that required movement of the whole body only when not using the upper extremities. Aiken, Fairbrother & Post (2012) also reported an effect of video feedback using a similar task.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, video feedback, including self-observation, allows self-monitoring and the self-correction of errors during task performance (Toglia & Kirk, 2000). Several studies have demonstrated the effects of video feedback on motor skill learning for healthy (Ste-Marie, Vertes, Law, & Rymal, 2012) and brain-damaged subjects (Schmidt, Fleming, Ownsworth, & Lannin, 2013). Thus, action observation and video feedback lead to enhanced motor skill learning by observing performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it appears that children that request feedback more often than their peers demonstrate enhanced learning (Chiviacowski, Wulf, Laroque de Medeiros, Kaefer, & Wally, 2008). And whereas adults tend to ask for feedback relatively infrequently, after a little more than 10% of the attempts (Janelle et al, 1997), children are reported to ask after one-third of the trials or more frequently (e.g., Ste-Marie et al, 2013). Clearly, it is impossible for a teacher to meet this need for feedback and additional attentional cueing with a group of over 20 children.…”
Section: A Hurdle For Self-controlled Feedback In Groupsmentioning
confidence: 99%